Defant's work on North Atlantic climate variability revisited - Stefan Brönnimann; Felix Frei (Meteorologische Zeitschrift, 2008)
In 1924, Albert Defant published an illuminating paper on North Atlantic climate variability. He identified and analysed the main modes of atmospheric circulation over the North Atlantic and compared corresponding index series with other geophysical time series (e.g., volcanic eruptions, sea ice, tropical circulation). This view was anticipating many aspects of the current perspective in research on North Atlantic climate variability and hence is an important forerunner. At about the same time, Sir Gilbert Walker published a number of articles on global climate variability, thereby taking a statistical point of view. In these papers he distinguished three major large-scale modes, one of which he termed the North Atlantic Oscillation (NAO). While Defant's work is not particularly well known, Walker's papers are often cited. Here we contrast the work of the two scientists and discuss possible reasons for the very different reception histories. To embed Defant's perspective in the current scientific debate, we revisit his approach, thereby making use of a much longer data record. We find that his approach of defining an index series is offering interesting perspectives to studying North Atlantic climate variability.